Primary biliary cholangitis with normal alkaline phosphatase: A neglected clinical entity challenging current guidelines. Issue 116 (January 2021) - Terziroli Beretta-Piccoli, Benedetta; Stirnimann, Guido; Mertens, Joachim; Semela, David; Zen, Yoh; Mazzucchelli, Luca; Voreck, Anja; Kolbus, Norbert; Merlo, Elisabetta; Di Bartolomeo, Claudia; Messina, Paola; Cerny, Andreas; et al.
Abstract: Background & aim: The diagnosis of primary biliary cholangitis (PBC), an uncommon immune-mediated cholestatic liver disease, is based on positive circulating anti-mitochondrial (AMA) and/or PBC-specific anti-nuclear autoantibodies (ANA), coupled with elevated serum alkaline phopsphatase (ALP) levels. Timely initiation of treatment with ursodeoxycholic acid prevents progression to cirrhosis and liver failure. We aimed at investigating liver histology in patients with normal ALP level and positive AMA and/or PBC-specific ANA. Methods: We searched the Swiss PBC Cohort Study database, which includes subjects with positive PBC autoimmune serology and normal ALP levels, for patients who underwent a liver biopsy. Histological slides were centrally reviewed by an expert liver pathologist, and sera were centrally re-tested for AMA and ANA. Results: 30 patients were included; 90% females, median age 53 (range 27–72) years. Twenty-four (80%) had liver histology typical for (n = 2), consistent with (n = 16) or suggestive of (n = 6) PBC, including three of four AMA-negative ANA-positive patients. Among 22 ursodeoxycholic acid treated patients, 14 had elevated GGT levels before treatment; a significant decrease of the median GGT level between pre- (1.46 x ULN) and post- (0.43 x ULN) treatment (p = 0.0018) was observed. Conclusions: In our series, a high proportion of AMA positive patients with normal ALP levels have PBC. For the first time we show histological diagnosis of PBC in AMA-negative/PBC-specific ANA-positive subjects and the potential role of GGT as a biomarker in PBC patients with normal baseline ALP levels. Current guidelines for the diagnosis of PBC do not cover the whole extent of PBC presentation, with important clinical implications in terms of timely treatment initiation. Highlights: 30 patients with positive PBC serology and normal alkaline phosphatase. 80% had histological PBC features. 3 of 4 AMA-negative/ANA-positive cases had PBC histology. Median GGT level significantly decreased on ursodeoxycholic acid treatment.